SIGNIFICANCE OF ENVIRONMENTAL FACTORS AND ADAPTIVE CAPABILITIES OF CHILDREN WITH RECURRENT EPISODES OF OBSTRUCTIVE BRONCHITIS - V.V. Karpov; M.G. Lukashevich; V.V. Kiselev; L.A. Safronenko; E.E. Makovkina; T.N. Surazakova (Вопросы современной педиатрии, 2008)
The objective of the study was to evaluate the level of significance of environmental factors (ecological and social), their interconnection with different somatic types and adaptive capabilities, as well as with peculiarities of preschoolers immunity with recurrent episodes of obstructive bronchitis (ob) to work out adequate therapy schemes for periods of exacerbation and rehabilitation. It is proven that children with recurrent ob are characterized by mesomacrosome somatotype, prevalence of vagotonia, sympathicotonia with hyper sympathicotonic type of vegetative reactivity and significant disorder of mucociliary clearance persisting after clinical recovery. The efficiency of ambroxol mugoregulator in complex therapy of ob and expedience of its long term (14–18) administration for recovery of disturbed system of mucociliary transport, were confirmed.Key words: obstructive bronchitis, children, somatotype, vegetative reactivity, immunity, ambroxol.